2007
DOI: 10.1158/0008-5472.can-06-3758
|View full text |Cite
|
Sign up to set email alerts
|

Active Induction of Tumor-Specific IgE Antibodies by Oral Mimotope Vaccination

Abstract: A role of IgE antibodies in cancer surveillance has been implicated for a long time. Studies dealing with IgE antibodies directly targeted to tumor antigens have shown marked anticancer effects mediated by this antibody class. Thus, the basic function of IgE antibodies may be to control tumor growth. Thus far, cancer-specific IgE has only been applied passively. Consequently, the aim of this study was to establish an active vaccination protocol to induce tumor antigenspecific IgE antibodies, and to evaluate fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 43 publications
0
30
0
1
Order By: Relevance
“…Oral immunization of mice with mimotopes of trastuzumab, an anti-human epidermal growth factor receptor (HER)-2 mAb, led to the development of HER-2-specific IgE. HER-2-specific IgE-bound tumor cells could be killed in vitro by FcRI ϩ effector cells (24). Our first approach in the study of an IgE-mediated immune response in the prevention and control of tumor growth relied on the in vitro or in vivo targeting of IgE on the surface of tumor cells by a three-step strategy (25).…”
mentioning
confidence: 99%
“…Oral immunization of mice with mimotopes of trastuzumab, an anti-human epidermal growth factor receptor (HER)-2 mAb, led to the development of HER-2-specific IgE. HER-2-specific IgE-bound tumor cells could be killed in vitro by FcRI ϩ effector cells (24). Our first approach in the study of an IgE-mediated immune response in the prevention and control of tumor growth relied on the in vitro or in vivo targeting of IgE on the surface of tumor cells by a three-step strategy (25).…”
mentioning
confidence: 99%
“…Jensen-Jarolim et al (33) showed that oral vaccination with a breast tumor "Ag" stimulates the production of IgE Abs that activate IgE effector cells and mediate tumor cell lysis in vitro. Reali et al (34) have shown that passive immunization with IgE Abs can also result in stimulating an active immune response.…”
mentioning
confidence: 99%
“…A number of groups have examined the concept of raising IgE antibodies through a number of active immunization approaches and also by harnessing powerful immune effector cell functions against cancer cells through passive immunotherapy with monoclonal antibodies (138,139,140,142,146,147,148,149,150,151,152,153). A growing number of studies, including those from our group, demonstrate the promise of activating allergic responses against cancer and have defined the emerging field of AllergoOncology (138,154,155).…”
Section: Concluding Remarks and Future Roles Of Antibodies In Therapymentioning
confidence: 99%